MANAJEMEN KEPALA MADRASAH DALAM MEWUJUDKAN MADRASAH HEBAT MANDIRI DAN BERPRESTASI PADA MTsN 2 SOLOK - Yulianti, Rani; Remiswal, Remiswal; Hidayati, Hidayati (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study is first, to find out the planning of the head of the madrasah in realizing an independent and outstanding madrasah at Madrasah Tsanawiyah Negeri 2 Solok; second, to find out the organization of the head of the madrasah in realizing an independent and outstanding madrasah at Madrasah Tsanawiyah Negeri 2 Solok; third, to find out the implementation of the head of the madrasah in realizing a great, independent and outstanding madrasah at Madrasah Tsanawiyah Negeri 2 Solok; and fourth, to find out the evaluation of the head of the madrasah in realizing a great, independent and outstanding madrasah at Madrasah Tsanawiyah Negeri 2 Solok. This research is a field research that uses qualitative methods with a descriptive approach. The techniques used in data collection are: observation, interview and documentation techniques. Data analysis used in this study are: data reduction, data presentation (data display), data checking (data verification), and drawing conclusions. This research found that the management of the head of the madrasah in realizing a great, independent and outstanding madrasah in MTsN 2 Solok has been going well, which is judging from four things, namely: first, planning carried out by means of good deliberation and cooperation between the head of the madrasah and all academics; second, the organization carried out has been carried out according to planning and the distribution of each task in accordance with the expertise and skills possessed; Third, in the implementation process, the head of the madrasah always takes part to provide direction and guidance; And fourth, the supervision carried out has been carried out effectively, because this supervision is useful to find out whether the planning, organizing, implementation has been carried out in accordance with the predetermined objectives in realizing an independent and outstanding madrasah.